Autorregulación para el aprendizaje en niños de cinco años en la Institución Educativa Inicial C.J N° 160 Mi Primer Aprendizaje, Caballococha 2021 - Cordova Silva, Gretha Veronica (2022)
This research was carried out with the purpose of describing the level of self-regulation for learning in five-year-old children in the Initial Educational Institution C.J Nº160 My First Learning of Caballo Cocha in the year 2021. As a methodology, the type of investigation was used descriptive, with a non-experimental, cross-sectional, field, and univariate design. The population and sample for the purposes of the study consisted of 80 children of five years of initial level. The data collection technique was observation, and an observation guide was applied as an instrument, previously validated through expert judgment. The conclusion of the investigation is that the level of self-regulation for learning in children of five years in the Initial Educational Institution C.J Nº160 My First Learning of Caballo Cocha; it is at 17.5% of good level; in 71.2% of regular level and in 11.3% of deficient level. What shows that the self-regulation of learning in children is at the regular level, so it is necessary to strengthen and improve these needs so that they achieve the good level.